1957
DOI: 10.1002/jsfa.2740081006
|View full text |Cite
|
Sign up to set email alerts
|

The caking of granular fertilizers: An investigation on a laboratory scale

Abstract: Preliminary consideration suggested a technique for studying the caking of granular fertilizers on a laboratory scale similar to that used in soil mechanics. An apparatus and technique were devised, and details of these are given. Time of storage of the fertilizer is found to be an important factor, and caking is rapid in the first few days. Preliminary investigations on the effect of chemical composition showed setting to be more serious when ammonium sulphate (I), superphosphate (2) and muriate of potash (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1961
1961
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…I t has been postulated (Irani et al, 1959) that as the temperature falls, the saturated solutions which are present on the surface undergo crystallization thus binding one particle to another. However, other investigations (Whynes & Dee, 1957;Lazar & Morgan, 1966) have found that caking is rather related to an increase in temperature. Particle size was reported to become a significant factor below 100 p, since small particles tend to adhere (Craik & Miller, 1958;.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…I t has been postulated (Irani et al, 1959) that as the temperature falls, the saturated solutions which are present on the surface undergo crystallization thus binding one particle to another. However, other investigations (Whynes & Dee, 1957;Lazar & Morgan, 1966) have found that caking is rather related to an increase in temperature. Particle size was reported to become a significant factor below 100 p, since small particles tend to adhere (Craik & Miller, 1958;.…”
Section: Introductionmentioning
confidence: 87%
“…If a material is relatively insoluble in water the effect of water on its caking characteristics is greatly decreased (Irani, Calls & Liu, 1959). Caking was found to be related to moisture content of granular fertilizers and it was greatly reduced by drying to less than 1% moisture content (Whynes & Dee, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…2) For powders which partially agglomerate because of moisture adsorption, the percentage of powder agglomerated may be measured (13)(14). 3) For powders which have caked completely, the compressive strength necessary to break the cake may be measured (15)(16)(17)(18)(19)(20)(21). 4) IIygroscopicity, which may be related to agglomeration, is measured, for instance, by measuring the critical relative humidity or water vapor pressure in equilibrium with powder (22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Ettle (713) used a penetrometer to detect caking in stored fcrtilizcr. U'hynes and Dee (77) have used a procedure adapted from the study of soil stability. I t measures the crushing strength of a cylinder of the preconditioned powder held in a rubber sleeve.…”
mentioning
confidence: 99%